INFLAMMATORY BOWEL DISEASE RISK STRATIFICATION AND MANAGEMENT IN A COMMUNITY PRACTICE SETTING. (22nd January 2022) - Collins, Angelina; Swift, Sadie; Recht, Adam; Prime, Rose; Topp, Robert; Beltyukova, Svetlana; Goldklang, Robert; Gaylis, Franklin
Abstract: INTRODUCTION: Risk stratification of patients with Inflammatory Bowel Disease (IBD) is integral for patient management according to care pathways and IBD guidelines. We examined explicit IBD risk stratification and the extent of its influence on patient management in a community-based practice setting. MATERIAL AND METHODS: This was a single-center, retrospective study of adult patients with IBD followed at Genesis Healthcare Partners between January 1, 2016 and December 31, 2018. 250 consecutive IBD charts were reviewed for (a) patient demographics; (b) disease characteristics; (c) explicit risk stratification and disease activity documented by clinician provider; (d) management and treatment. Patients were independently risk stratified based on AGA clinical care pathway risk factors (implicit risk stratification). CD high risk factors include: age under 30 at diagnosis, extensive anatomic involvement, perianal and/or severe rectal disease, deep ulcers on endoscopy, stricturing and/or penetrating behavior, prior surgical resection. UC high risk factors include age under 40 at diagnosis, extensive anatomic involvement, deep ulcers on endoscopy, high CRP and/or ESR, steroid requiring disease, C Difficile or CMV infection, prior hospitalization for UC. RESULTS: 211 eligible patients: 77 (36.5%) with Crohn's Disease (CD) and 134 (63.5%) with Ulcerative Colitis (UC) were included; 52% female, 85% Caucasian, median age at diagnosis was 33 years, median length of CD was 16 years, and the median length of UC was 8 years. 18 (2%) had explicit risk stratification documented. Implicit risk stratification was: CD: 9 (12%) low risk [zero high risk factors], 68 (88%) high risk [one or more high risk factors]. UC: 27 patients (20%) low risk [zero high risk factors]; 107 patients (80%) high risk [one or more high risk factor]. Medication management for low-risk CD : 5-ASAs: 5 (56%); locally acting steroids: 5 (56%); systemic steroids: 1 (11%); immunomodulators (IMM): 2 (22%); and biologics: 4 (44%) and high-risk CD : 5-ASAs: 17 (25%); locally acting steroids 18 (27%); systemic steroids 20 (30%); IMM: 21 (31%); biologics: 46 (69%). Medication management for low-risk UC : 5-ASAs: 24 (92%); locally acting steroids: 5 (19%); systemic steroids: 4 (15%); IMM: 2 (8%); biologics: and 1 (4%) and high-risk : 5-ASAs: 97 (91%); locally acting steroids: 42 (39%); systemic steroids: 45 (42%); IMM: 16 (15%); biologics: 44 (41%). Of 182 UC endoscopy procedures explicit Mayo endoscopic sub-scores was documented in 3 (2%). Implicit Mayo Scoring was: 21% Mayo 0, 34% Mayo 1, 26% Mayo 2 and 16% Mayo 3. CONCLUSIONS: Explicit risk stratification and Mayo endoscopy scoring was infrequently documented. Embedding risk stratification tools and standardized Mayo endoscopy scoring into EMRs would help to standardize documentation.